Erratum: ANDREW D. CORSO, THOMAS DESVIGNES, JAN R. MCDOWELL, CHI-HING CHRISTINA CHENG, ELLEN E. BIESACK, DEBORAH K. STEINBERG & ERIC J. HILTON (2024) Akarotaxis gouldae, a new species of Antarctic dragonfish (Notothenioidei: Bathydraconidae) from the western Antarctic Peninsula. Zootaxa, 5501 (2): 265–290. - Corso, Andrew D.; Desvignes, Thomas; Mcdowell, Jan R.; Cheng, Chihing Christina; Biesack, Ellen E.; Steinberg, Deborah K.; Hilton, Eric J. (Zootaxa, 2026)
N/A